Krshi thoka bajāra sthāpanā sambhāvyatā adhyayana prativedana, Parsā Jillā (Śri 5 ko Sarakāra, Khādya, Krshi, tathā sīncāī Mantrālaya, Khādya tathā Krshi Bajāra Sevā Vibhāga, Bajāra Sevā Śākhā, 1977)
Feasibility study on the establishment on a wholesale market in Parsa District, Narayani Zone, Nepal.